(untitled) (SAARC Journal of Agriculture, 2020)
The aim of this study was to estimate different body measurements and derive prediction equation for live weight of Jamuna basin sheep using different body measurement. A total of 520 individual records of sheep (47 males and 473 females) including all temporary at nine-month age (320), first pair permanent at 1.6 year age (161) and 2nd pair permanent at two years age (39) were collected from two Upazila of Sherpur district. Body weight (BW) was taken using a weighing scale and different measurements were taken using the tailor’s tape measure and measuring stick while animals were on standing position. Data were analyzed with the help of SPSS-v-20 computer package program. Average BW, wither height(WH), rump height(RH), body length(BL), sternum height(SH), body depth(RD), bi-costal diameter(BD), ear length(EL), rump width(RW), head width(HW), rump length(RL), head length(HL), heart girth(HG), cannon bone circumference(CC) and muzzle diameter(MD) were 12.28±2.75 kg, 49.42±3.78, 54.04±3.88, 49.38±4.57, 28.06±3.00, 53.09±4.40, 15.07±2.58, 8.66±3.32, 15.72±2.33, 12.87±2.20, 14.30±2.29, 18.23±2.30, 55.02±4.71, 9.22±1.01, and 16.65±1.73cm, respectively. According to sex BW, WH, RH, SH, RD and CC were found significant (p<0.001), HG and MD were found significant(p<0.01). Stepwise multiple regression analysis according to agein all temporary groups showed that the body weight was found the best fitted equation having the highest R2value 64% (BW = - 15.53+0.24HG+0.13WH+0.16BD-.1RW+0.05EL) whereas in 1.3-1.6 and 1.9-2 years age group the R2 value for BD was 56 (BW = - 15.65+0.31HG+0.22WH)and 83% (BW = -24.51+0.21RH+0.35HG+0. 19BL-0.78RL+1.2RW-0.87HW), respectively. R2value for BD in male (BW = -28.91+0.43HG+0.35WH) and female (BW = -10.62+0.27HG+ 0.13WH+0.06BD-0.13HW+0.07BL-0.10SH-0.10RL) was 88and 59%, respectively. It is concluded that the best prediction parameter of BW was HG, WH, BD, RW, EL, RH, BL and HW. SAARC J. Agri., 18(1): 183-196 (2020)